2015
DOI: 10.1111/1365-2664.12437
|View full text |Cite
|
Sign up to set email alerts
|

Fire and non‐native grass invasion interact to suppress tree regeneration in temperate deciduous forests

Abstract: Summary1. While many ecosystems depend on fire to maintain biodiversity, non-native plant invasions can enhance fire intensity, suppressing native species and generating a fire-invasion feedback. These dynamics have been observed in arid and semi-arid ecosystems, but fire-invasion interactions in temperate deciduous forests, where prescribed fires are often used as management tools to enhance native diversity, have rarely been investigated. 2. Here we evaluated the effects of a widespread invasive grass on fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 30 publications
0
27
1
Order By: Relevance
“…fire temperatures or flame height), native seed survival, tree survival and growth, or invader populations (Flory et al . ). In addition, the fires were conducted in one quadrant of the plots, which were already limited in size, and fire behaviour and effects may vary based on the spatial scale of fires.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…fire temperatures or flame height), native seed survival, tree survival and growth, or invader populations (Flory et al . ). In addition, the fires were conducted in one quadrant of the plots, which were already limited in size, and fire behaviour and effects may vary based on the spatial scale of fires.…”
Section: Discussionmentioning
confidence: 97%
“…Microstegium can have direct effects during the growing season via competition and indirect effects through dense litter accumulation, which can hinder native seedling recruitment (Flory & Clay ), and cause more intense fires and exacerbate fire effects on native species (Flory et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…Flory et al . () showed that maximum fire temperatures were on average 57% greater in sites invaded by M. vimineum than in uninvaded control areas. In addition, fires burned at temperatures of over 300 ° C for nearly twice as long and flame heights were 98% higher in invaded compared with uninvaded habitats.…”
Section: Impactmentioning
confidence: 99%
“…Conclusion cycle" (Setterfield et al 2010;van Klinken et al 2013;Wagner and Fraterrigo 2015) due to the increases in the abundance of fine fuels. With increases in fire frequency and intensity (D'Antonio and Vitousek 1992), a decrease in native tree and shrub cover and abundance can result, which will further facilitate more grass invasion, further increasing the risk of higher intensity and more frequent fires resulting in an ever increasing self-perpetuating fire cycle (Flory et al 2015). Introduced grass invasion is likely to result in substantial changes to fire regimes in invaded ecosystems, as these fire promoting grasses are ecosystem transformers that have the potential to alter the community structure (RossiterRachor et al 2016 Ecosystem transformation can also occur with a reduction in fire frequency and intensity, where fire is or has been withheld and there is a change in fire management, as Chapter 5…”
Section: Resultsmentioning
confidence: 99%
“…The grass-fire cycle occurs when alien grass invades an area and increases the abundance of fine fuels, which increases fire frequency and intensity (D'Antonio and Vitousek 1992). This can result in a decrease in native tree and shrub cover and abundance, which further facilitates more grass invasion, which in turn increases the risk of future higher intensity and frequency of wildfires in an ever increasing self-perpetuating fire cycle (Flory et al 2015). found that Mission grass fuel loads were approximately five times greater than that of native grasses.…”
Section: Discussionmentioning
confidence: 99%